SEASONAL CHANGES IN THE TEMPERATURE, SALINITY AND PLANKTON VOLUME AT PORT BLAIR, ANDAMANS - Rengarajan, K; Marichamy, R (Indian Journal of Fisheries, 2011)
The seasonal changes in the temperature, salinity and plankton volumeat Port Blair, Andamans, during the period 1964 to 1970 have been investigatedand the changes correlated with the meteorological conditions of the locality.The atmospheric temperature exhibited a clear double oscillation in a year, themaxima occurring in April and November. The range of fluctuation was generallyless than 10Â°C. The surface temperature closely followed the atmospherictemperature and exhibited a clear double oscillation. The surface temperaturewas invariably lower than the atmospheric temperature. The temperature ofthe surface water steadily increased from January to April registering a sharpfall in May due to the onset of the south-west monsoon. The surface salinityincreased steadily from January to April registering a fall in May which coincidedwith the onset of the monsoon. Higher values were restored during thepost-monsoon period. The surface water was fairly rich in plankton during thecolder months. An inverse relationship was noticed between the abundance ofplankton and temperature/salinity.